Lexical access mechanisms of Indonesian speakers: A study case of a daily conversation in a college - Hirlina Nailul Muna; Asngadi Rofiq (Universitas Muhammadiyah Purwokerto, 2026)
This study aims to examine the mechanisms of lexical access in native speakers from a neurolinguistic perspective, with a particular focus on the processes of activation and selection of lexical representations in spontaneous spoken discourse. This research employs a descriptive qualitative approach, with data consisting of naturally occurring utterances produced by five native speakers of Indonesian. The data were collected through recorded conversations and analyzed by identifying surface-level linguistic markers, such as pauses, repetitions, self-repairs, and lexical stress, which reflect the dynamics of lexical access. The findings indicate that the process of lexical activation does not occur in a linear manner; rather, it involves competition among lexical representations prior to the final selection stage. This phenomenon is theoretically consistent with models of speech production that emphasize the interaction between activation and lexical selection control. This study contributes to theoretical neurolinguistics by presenting an analysis based on natural speech data in the context of the Indonesian language. The findings enrich the understanding of lexical access mechanisms in spontaneous speech production and demonstrate that surface-level linguistic phenomena can serve as a basis for interpreting cognitive processes in language production. The novelty of this study lies in its examination of lexical access mechanisms based on spontaneous spoken data, positioning lexical stress as a prosodic indicator of the lexical selection stage—an aspect that has rarely been addressed in previous neurolinguistic studies, which are generally based on experimental tasks.